Effects of Yishen Pinggan Recipe on Renal Protection and NF-κB Signaling Pathway in Spontaneously Hypertensive Rats. (16th March 2016) - Luo, Guodong; Zhu, Xiying; Gao, Zhongxiang; Ge, Huaxun; Yu, Yang; Guo, Yuanyuan; Zheng, Jian-Pu; Liu, Longmin
Abstract : Inflammation is an important etiological factor of hypertensive renal damage. The effects of Yishen Pinggan Recipe (YPR) on urine microalbumin, histology, and NF- κ B/P65, I κ B- α, IL-1 β, IL-6, and TNF- α in renal tissues were evaluated in SHR to explore the mechanism of its renal protection in hypertensive renal damage. The SBP of 12-week-old SHR was192.41 ± 3.93  mmHg and DBP was142.38 ± 5.79  mmHg. Without treatment, the 24-week-old SHRs' SBP was196.96 ± 3.77  mmHg and DBP was146.08 ± 4.82  mmHg. After the 12-week-old SHR were administered YPR for 12 weeks, the rats' SBP was161.45 ± 7.57  mmHg and DBP was117.21 ± 5.17  mmHg; YPR could lower blood pressure in SHR. And renal function damage was observed in 24-week-old SHR without treatment, manifested as urine protein and morphological changes which could be inhibited by YPR. In addition, YPR could reduce the expression of inflammatory cytokines (IL-1 β, IL-6, and TNF- α ) in kidneys. It could also inhibit the nuclear translocation of NF- κ B p65 and degradation of I κ B- α in renal cells, indicating that the NF- κ B signaling pathway was inhibited by YPR. Finally, the study suggests that YPR could significantly improve the renal function in SHR. The mechanism could be attributed to its inhibition of renal NF- κ B signaling pathway and inflammation.